TO ASSESS THE EFFECT OF YAPANBASTI IN AGNIMANDYA AND DEHABALAKSHAYA- A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda has a variety of ways for manifestations and managements for different Vyaadhis. Ayurveda believes that diseases occur mainly due to disturbance in Jatharagni (digestive fire). So in order to cure any disease, Agni is one of the important factors to be concentrated. Similarly, the Dehabala (strength of the body) is also important for healthy lifestyle. In order to normalize the Agni and Dehabalakshaya, various methods are given in Ayurvedic Classics. Panchakarma is one of them. In Panchakarma, Basti is said to be the best and can be used in almost all the Vyaadhis. Yapanbasti mentioned in classics is one of the types of Basti which can be used in the management of Agnimandya and for increasing Dehabala. A case study was taken for research having complaints of Agnimandya and Dehabalakshaya. Written informed consent was taken and Basti Poorvakarma, Pradhankarma and Paschatkarma were done for 8 days. Observation and results: Jaranshakti, Abhyavaharanshakti, Ruchi, Vatamalamutramukti, Balavriddhi and Swaravarnayoga were improved. However, there was no significant change in weight. Discussion: Yapanbasti if given for more than 8 days may be effective in increasing the weight. It is easy to administer it by considering today’s busy schedule. It can be given in almost all the diseases. Conclusion: Yapanbasti is effective in Agnimandya and Dehabalakshaya. Summary: Yapanbasti is a Niruha Basti which can be used for the management of Agnimandya and for increasing Dehabala.